An analysis of the traditional Alto dos Coelho community by the method geoethnographic / Uma análise da comunidade tradicional Alto dos Coelhos pelo método geoetnográfico - Patrícia Quirino Rocha; Angela Fagna Gomes de Souza; José Rodolfo da Silva Santos; Felipe Santos Silva; Maria de Almeida Soares; Ívia Rejane Ferreira Silva (Universidade Estadual de Alagoas, 2017)
This article aims to score as ethnography can be used as a methodological approach to geographical research and in particular for target studies how on traditional communities. Ethnography is a method often used by anthropologists in the effort to know the detail and density of the research object of study, for example, traditional communities, tribes, villages or quilombos. Geography come seizing of methods of other sciences and anthropology is one of them. The junction of anthropological method, ethnography, with the geographic approach is what we call geo etnografia. This interaction intend to achieve success understanding the dynamics of traditional communities. The authors we used for theoretical support were Souza (2013), Neves (2006), Turato (2003) and Chizzotti (2008) who are serious researchers in their research using ethnography as methodology and additionally develop approached research.